(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Self-esteem is a significant component in clinical, developmental, personality, and social psychology. Its role in psychological functioning has been studied for nearly a century. The concept of self-esteem has evolved. Produced a study literature with such breadth and depth that keeping up with it is challenging